2013
DOI: 10.4049/jimmunol.1300990
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Targets β2 Integrin Expression To Suppress Monocyte Adhesion

Abstract: Chronic recruitment of monocytes and their subsequent migration through the activated endothelium contribute to atherosclerotic plaque development. Integrin-mediated leukocyte adhesion is central to this process. Conjugated linoleic acid (CLA) has the unique property of inducing regression of pre-established murine atherosclerosis via modulation of monocyte/macrophage function. Understanding the mechanisms through which CLA mediates its atheroprotective effect may help to identify novel pathways that limit or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Further, intercellular adhesion molecule (ICAM) 1, TNF-α and interleukin (IL) 6 mRNA expression as well as superoxide generation in the aorta declined in mice treated with GYY4137 (Liu et al, 2013). Similarly, and again paralleling in vitro studies with human monocytes, CLA treatment of Apoe −/− mice with already pre-established atherosclerosis induced lesion regression by reducing leukocyte adhesion and decreasing CD18 expression on classical monocytes (De Gaetano et al, 2013). …”
Section: The Cxcl12/cxcr4 Axis In Cad: Identifying Potential Functionmentioning
confidence: 71%
See 1 more Smart Citation
“…Further, intercellular adhesion molecule (ICAM) 1, TNF-α and interleukin (IL) 6 mRNA expression as well as superoxide generation in the aorta declined in mice treated with GYY4137 (Liu et al, 2013). Similarly, and again paralleling in vitro studies with human monocytes, CLA treatment of Apoe −/− mice with already pre-established atherosclerosis induced lesion regression by reducing leukocyte adhesion and decreasing CD18 expression on classical monocytes (De Gaetano et al, 2013). …”
Section: The Cxcl12/cxcr4 Axis In Cad: Identifying Potential Functionmentioning
confidence: 71%
“…In addition, CLA reduced CXCR4 expression, resulting in an only minor initiation of “inside out” signaling. As a result, partial, but incomplete, activation of β 2-integrins further reduces adherence of leukocytes and their migration to CXCL12 (De Gaetano et al, 2013). …”
Section: The Cxcl12/cxcr4 Axis In Cad: Identifying Potential Functionmentioning
confidence: 99%
“…Multiple studies over the years have identified ICAM1 as a critical regulator of leukocyte arrest and transendothelial migration to allow leukocyte tissue infiltration in cardiovascular disease . In the human heart, endothelial ICAM1 is upregulated after myocardial infarction, correlating with high infiltration of inflammatory leukocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid mediators, resolvin D2, and maresin-1 inhibited expansion of the necrotic core, accumulation of macrophages, induced plaque stability, and shifted the M1:M2 macrophage ratio toward a reparative phenotype (42). Our previous work has shown that CLA 80:20 promotes anti-inflammatory macrophages, reduces inflammatory mediators, and alters monocyte responses to atherosclerotic stimuli (26,27,30,31). In this present study, novel phenotypic profiling of monocyte/macrophage phenotypes was performed in an early model of atherosclerosis with dietary CLA 80:20 blend.…”
Section: Discussionmentioning
confidence: 95%
“…Arbonés-Mainar et al showed that cis-9:trans-11-CLA inhibited atherogenic development, whereas Mitchell et al (28,29) reported trans-10:cis-12-CLA inhibited lesion development despite adverse CV profiles. We have previously interrogated the effects of CLA on macrophage phenotype and function and have shown that CLA 80:20 induces an atheroprotective M2 macrophage phenotype (27) and limits foam cell formation, monocyte adhesion, and the inflammatory phenotype associated with monocytes and macrophages in atherosclerotic disease (30,31).…”
mentioning
confidence: 99%